XVIIINew Literatures. (29th October 2018) - Daymond, Margaret; Gui, Weishin; Griffiths, Michael; Lorre-Johnston, Christine; McNeill, Dougal; Nelson, Ashlee; Niblett, Michael; Raja, Ira; Sharrad, Paul; Spencer, Lynda; Steiner, Tina; Williams, Mark
Abstract: This chapter has seven sections: 1. Africa; 2. Australia; 3. Canada; 4. The Caribbean; 5. South Asia: The Indian Subcontinent and Sri Lanka; 6. New Zealand and Pacific; 7. Southeast Asia. Section 1 is by Margaret Daymond, Ashlee Nelson, Lynda Spencer, and Tina Steiner; section 2 is by Paul Sharrad and Michael Griffiths; section 3 is by Christine Lorre-Johnston and Mark Williams; section 4 is by Michael Niblett and Mark Williams; section 5 is by Ira Raja and Mark Williams; section 6 is by Dougal McNeill; section 7 is by Weishin Gui.